2012
DOI: 10.1371/journal.pbio.1001258
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of the World's Sheep Breeds Reveals High Levels of Historic Mixture and Strong Recent Selection

Abstract: Genomic structure in a global collection of domesticated sheep reveals a history of artificial selection for horn loss and traits relating to pigmentation, reproduction, and body size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

115
968
11
23

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 701 publications
(1,151 citation statements)
references
References 54 publications
115
968
11
23
Order By: Relevance
“…For low heritability traits, a very large number of records will be required in the TS to subsequently achieve high accuracies of GEBV in unphenotyped animals. If we consider our SBF population, where the effective population size (Ne) is~500 (Kijas et al, 2012), then according to the formula suggested by Daetwyler et al (2010b) to achieve an accuracy of 0.6, we would need 30 000 individuals for a trait with very low heritability (e.g. Nematodirus FEC at 16 weeks), and~5000 for a trait with moderate heritability (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For low heritability traits, a very large number of records will be required in the TS to subsequently achieve high accuracies of GEBV in unphenotyped animals. If we consider our SBF population, where the effective population size (Ne) is~500 (Kijas et al, 2012), then according to the formula suggested by Daetwyler et al (2010b) to achieve an accuracy of 0.6, we would need 30 000 individuals for a trait with very low heritability (e.g. Nematodirus FEC at 16 weeks), and~5000 for a trait with moderate heritability (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the number of SNPs needed to predict unrelated individuals is equal to 10 NeL, where L is the length of the genome in Morgans (Meuwissen, 2009). In the SBF population, with Ne of~500 (Kijas et al, 2012) and L of approximately 27 Morgans, predictions for unrelated individuals would require at least 135 000 SNPs. This marker density may be achievable with the forthcoming high-density sheep SNP chip.…”
Section: Discussionmentioning
confidence: 99%
“…We assumed that 100 Mb ¼ 1 Morgan (as for example in Kijas et al, 2012). We estimated average values of r 2 in 20 distance classes between 2.5 kb and 1 Mb (corresponding to 0.0025-1 cM).…”
Section: Estimation Of Past Demographic Changes In European Wolf Popumentioning
confidence: 99%
“…A genome-wide association study (GWAS) of most of the world's sheep breeds revealed that the KIT, ASIP, and MITF genes that determine the sheep coat color have been under strong selection (Kijas et al, 2012). However, ASIP, which controls a series of alleles of black and white coat color, was not detected in a new GWAS of sheep selection (Zhang et al, 2013), although they used a different sheep breed.…”
Section: Discussionmentioning
confidence: 99%